ANÁLISIS DE LA PLANIFICACIÓN CURRICULAR DE ANATOMÍA Y FISIOLOGÍA HUMANA COMPARADA PARA EL DESARROLLO DE LOS APRENDIZAJES SIGNIFICATIVOS DE LOS ESTUDIANTES DE CUARTO AÑO DE CIENCIAS: BIOLOGÍA, QUÍMICA Y LABORATORIO DE LA UNACH, PERIODO 2012-2013. - Yagos Cuzco, José Luis (2014)
The research was conducted at the National University of Chimborazo in school Science specialty of Biology, Chemistry and Laboratory in the city of Riobamba, the goal was: ―To determine the analysis of curriculum planning of Comparative Physiology Human Anatomy and development of the meaningful learning of students in the fourth year of science: Biology, Chemistry and Laboratory UNACH, period 2012-2013.‖ The research was raised through a non-experimental design, explanatory type. Besides this we used the scientific method to the development of the theoretical framework and see theoretically the teaching and learning process. Thus, from observation and research we develop the theoretical foundations, check results and make conclusions and recommendations. The techniques and tools that were applied to the students of Science: Biology, Chemistry and Laboratory allowed us to know the criteria of the students about how the subject of Human Anatomy and Physiology Comparative currently is developed and propose activities that strengthen the meaningful learning. Alternatively a proposal was raised where students use labs to reinforce the degree of learning that they have in the subject. By implementing the Lab Guide, the results were positive, and objectives established at the beginning of the investigation were completed. The conclusions reflect the need that teachers should improve and create new ways to undertake a significant, dynamic and inclusive learning according to the demands of education in the XXI century.